Effective Police Station Legal Advice - Country Report 4: The Netherlands - Maegherman, Enide; Vanderhallen, Miet (University of Nottingham, 2018)
This Country Report for the Netherlands has arisen out of a comparative study into police station legal advice, led by Dr Vicky Kemp, University of Nottingham. She received a small grant from the British Academy/Leverhulme to undertake semi-structured interviews with defence lawyers and policy officers responsible for criminal legal aid in six jurisdictions: Belgium, England and Wales, Ireland, the Netherlands, Northern Ireland and Scotland. Dr Miet Vanderhallen was the consultant responsible for the research being undertaken in Belgium and the Netherlands, assisted by Enide Maegherman, both from the University of Maastricht.